THE EFFECTIVITY OF CITRONELLA AND CLOVE OILS AGAINTS CABBAGE CATERPILLAR Crocidolomia pavonana - Rismayani Rismayani; I Wayan Laba (Pusat Penelitian dan Pengembangan Perkebunan, 2015)
Crocidolomia pavonana is a major pest on cabbage crops. The use of chemical pesticides in pest control of C. pavonana is not the proper solution due to the fact that the chemical pesticides are not environmentally friendly, kill natural enemies and have negative impacts on human health. The aim of this study is to determine the effectiveness of the botanical pesticide consisting of citronella and eugenol oils to control C. pavonana. The treatment was conducted by using two methods based on the control target, firstly is direct spray, the larvae were sprayed and then infested onto cabbage plants. The second method is indirect spray, the larvae was infested onto cabbage plants after the plants were sprayed with botanical pesticide of cittronella and eugenol. Insect mortality was observed at 1; 3; 6; 24; 48; 72 and 96 hours after applications. The results show that the botanical pesticide of citronella and eugenol at concentration of 4.0 ml l-1 respectively was able to effectively control of C. pavonana pest on cabbage leaves.